2019
DOI: 10.1142/s0218271819501098
|View full text |Cite
|
Sign up to set email alerts
|

Entropy relations and bounds of BTZ black hole in gravity's rainbow

Abstract: In this paper, we present the entropy relations and bounds of Banados–Teitelboim–Zanelli (BTZ) black hole in two models of gravity's rainbow. Because of the effect of gravity's rainbow, one can find that the entropy product and sum both lost their universality and become mass-dependent. On the other hand, comparing the entropy bound of event horizon to the BTZ case, it is shown that the angular momentum [Formula: see text] enlarges the entropy bound while the gravity's rainbow parameter [Formula: see text] dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…It has been also shown that the thermodynamics of BTZ BHs can be deformed in the frame of gravity's rainbow, however, the Gibbs free energy remains unchanged [44]. The gravity of the rainbow has been utilized to study the BH heat capacity and phase transition of BTZ BHs [45,46]. There are also some other extensions of the BTZ BHs that are obtained as alternative theories of gravity for example the Noether symmetries of the rotating BTZ BH in f (R) gravitation has been employed to create new BTZ-type solutions [47].…”
Section: Introductionmentioning
confidence: 99%
“…It has been also shown that the thermodynamics of BTZ BHs can be deformed in the frame of gravity's rainbow, however, the Gibbs free energy remains unchanged [44]. The gravity of the rainbow has been utilized to study the BH heat capacity and phase transition of BTZ BHs [45,46]. There are also some other extensions of the BTZ BHs that are obtained as alternative theories of gravity for example the Noether symmetries of the rotating BTZ BH in f (R) gravitation has been employed to create new BTZ-type solutions [47].…”
Section: Introductionmentioning
confidence: 99%
“…Gravity's rainbow has been also exploited to study the black hole heat capacity and phase transition of BTZ black holes in Refs. [42,43]. There are also some other extensions of the BTZ black holes that are derived in alternative theories of gravity.…”
Section: Introductionmentioning
confidence: 99%
“…The rainbow gravity has been also exploited to study the black hole heat capacity and phase transition of BTZ black holes in Refs. [40,41]. There are also some other extensions of the BTZ black holes that are derived in alternative theories of gravity.…”
Section: Introductionmentioning
confidence: 99%